Transcriptional and functional predictors of potato virus Y-induced tuber necrosis in potato (Solanum tuberosum) - Manasseh, Richard; Sathuvalli, Vidyasagar; Pappu, Hanu R. (Frontiers in Plant Science, 2024)
Potato (Solanum tuberosum L.), the fourth most important food crop in the world, is affected by several viral pathogens with potato virus Y (PVY) having the greatest economic impact. At least nine biologically distinct variants of PVY are known to infect potato. These include the relatively new recombinant types named PVY NTN and PVY N-Wi , which induce tuber necrosis in susceptible cultivars. To date, the molecular plant-virus interactions underlying this pathogenicity have not been fully characterized. We hypothesized that this necrotic behavior is supported by transcriptional and functional signatures that are unique to PVY NTN and PVY N-Wi .To test this hypothesis, transcriptional responses of cv. Russet Burbank, a PVY susceptible cultivar, to three PVY strains PVY O , PVY NTN , and PVY N-Wi were studied using mRNA-Seq. A haploid-resolved genome assembly for tetraploid potato was used for bioinformatics analysis.The study revealed 36 GO terms and nine KEGG pathways that overlapped across the three PVY strains, making them generic features of PVY susceptibility in potato. Ten GO terms and three KEGG pathways enriched for PVY NTN and PVY N-Wi only, which made them candidate functional signatures associated with PVY-induced tuber necrosis in potato. In addition, five other pathways were enriched for PVY NTN or PVY N-Wi . One carbon pool by folate was enriched exclusively in response to PVY NTN infection; PVY N-Wi infection specifically impacted cutin, suberine and wax biosynthesis, phenylalanine metabolism, phenylalanine, tyrosine and tryptophan biosynthesis, and monoterpenoid biosynthesis. Results support that PVY N-Wi -induced necrosis may be mechanistically distinguishable from that of PVY NTN . Our study provides a basis for understanding the mechanism underlying the development of PVY-induced tuber necrosis in potato.